Entwicklung von Unterrichtsmaterial: Erfahrungen aus Amharisch-Intensivkursen - Kellermann, Petra (Aethiopica, 2019)
My Ethiopian colleague Seid Ahmed Ali and I have been teaching Amharic intensive courses at the Bundessprachenamt (Federal Office of Languages) since 2006. After the first course, we started to develop our own material based on existing textbooks. In this article I report on our experiences in teaching such courses and in developing our own teaching materials.